Pessoa, utopia e formação de professores - Alva, Blanca Beatriz Díaz (Educar em Revista, 2002)
Nesse artigo são analisados, a partir da perspectiva da desumanização do ser humano pela sociedade tecnológica, o homem-pessoa, as relações entre pessoa e sociedade e o homem como ser utópico, a fim de promover uma reformulação da formação de professores para uma prática reflexiva, crítica e ética, no intuito de recuperar o ser do homem no processo educacional. Individual, utopia and teachers formation Abstract In this paper, human being-person, the person-society relationships, and the man as an utopic being are analysed, according to the perspective of the human being losses of humanization for the technological society. It aims to discuss a reformulation of teachers professional preparation towards a reflexive, critical and ethical practice, whose purpose is to recover the human condition in the educational process.